Editorial - Agnieszka Żur; Maria Urbaniec (Entrepreneurial Business and Economics Review)
This issue marks another step in our growth as an international journal devoted to entrepreneurship aspects. This thematic issue is titled Advancing Research in Entrepreneurship and consists of nine thematic articles and four nonthematic articles.